How Social Media and Word Of Mouth Escalating The Brands: A Case Study at Cipondoh Healthy Pregnancy Clinic - Baiq yuliana Andriani Putri; Tantri Yanuar Rahmat Syah; M. Reza Hilmy (Journal of Multidisciplinary Academic, 2021)
The tight competitiveness of business requires the clinic to compete in promoting its various types of services. Hence, social media platforms on a smartphone can be utilized as one of the marketing strategies for companies and users to create content. Word of mouth (WOM) is the right way to promote clinics to be more widely known by the public. This research aims to analyze the marketing strategy of Cipondoh Healthy Pregnancy Clinic in developing customers positive attitudes to win the market. The research method is quantitative research with a cross-sectional study type. The research sample involves 200 people by using the purposive sampling technique. The research data analysis method is the Structure Equation Model (SEM) with Lisrel software. The results of the research show that Firm Created Content, User Generated Content, Word Of Mouth have a positive effect on brand image and brand attitude. The management implication is to build a strong brand community and relationship marketing.